2018
DOI: 10.1371/journal.pone.0198810
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practices about zoonotic tuberculosis prevention and associated determinants amongst livestock workers in Nigeria; 2015

Abstract: Zoonotic tuberculosis (TB) is a significant public health disease, but has long been neglected. Information on knowledge and practices of its prevention and influencing factors amongst occupationally exposed individuals is required for designing all-inclusive, informed control programmes. We investigated knowledge and practices related to zoonotic TB prevention and associated determinants amongst herdsmen and abattoir workers in south-western, south-eastern and north-western Nigeria using semi-structured quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
22
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 23 publications
9
22
2
1
Order By: Relevance
“…Similar conditions are prevailing in Pakistan. The results of present study are in contrary to those of [16] who conducted study in Nigeria during 2015.They found that respondents were good in knowledge about zoonotic TB prevention but they avoid demonstrating good practice. The ration of good practice was almost half of the respondent knowledgeable.…”
Section: Socio-demographic Characteristics Of Respondentscontrasting
confidence: 99%
“…Similar conditions are prevailing in Pakistan. The results of present study are in contrary to those of [16] who conducted study in Nigeria during 2015.They found that respondents were good in knowledge about zoonotic TB prevention but they avoid demonstrating good practice. The ration of good practice was almost half of the respondent knowledgeable.…”
Section: Socio-demographic Characteristics Of Respondentscontrasting
confidence: 99%
“…Expectedly, longer contact time with animals increases the chances of being infected with animal pathogens. This is supported by a previous report which showed that cattle handlers with longer duration in cattle handling had higher chances of being infected with bTB than those who had spent lesser time [ 33 ]. However, livestock workers, in general, lack adequate knowledge of bTB prevention [ 33 ].…”
Section: Discussionsupporting
confidence: 80%
“…This is supported by a previous report which showed that cattle handlers with longer duration in cattle handling had higher chances of being infected with bTB than those who had spent lesser time [ 33 ]. However, livestock workers, in general, lack adequate knowledge of bTB prevention [ 33 ]. Worse still, practices that enhance bTB transmission, such as consumption of unpasteurized milk and processing of infected carcasses, are prevalent among the occupationally exposed individuals [ 33 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…More importantly, these workers are generally uneducated, exhibit poor hygiene practices, indulge in alcoholism, drug addiction and have poor medical care-seeking behavior. A recent study revealed important knowledge gaps with poor practices about zoonotic TB prevention among livestock workers in Nigeria [ 8 ]. Coupled with these are the poor state of infrastructures at the cattle markets and abattoirs/slaughter slabs settings where they work [ 9 ], which are factors that could facilitate transmission of TB within the human-animal ecosystem interface in Nigeria.…”
Section: Introductionmentioning
confidence: 99%